If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y * 6 + 109 = Y * 11 + -11 Reorder the terms for easier multiplication: 6Y + 109 = Y * 11 + -11 Reorder the terms: 109 + 6Y = Y * 11 + -11 Reorder the terms for easier multiplication: 109 + 6Y = 11Y + -11 Reorder the terms: 109 + 6Y = -11 + 11Y Solving 109 + 6Y = -11 + 11Y Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-11Y' to each side of the equation. 109 + 6Y + -11Y = -11 + 11Y + -11Y Combine like terms: 6Y + -11Y = -5Y 109 + -5Y = -11 + 11Y + -11Y Combine like terms: 11Y + -11Y = 0 109 + -5Y = -11 + 0 109 + -5Y = -11 Add '-109' to each side of the equation. 109 + -109 + -5Y = -11 + -109 Combine like terms: 109 + -109 = 0 0 + -5Y = -11 + -109 -5Y = -11 + -109 Combine like terms: -11 + -109 = -120 -5Y = -120 Divide each side by '-5'. Y = 24 Simplifying Y = 24
| -4(-6)=(-9+y)(-2) | | (8y+9)(8y-9)= | | -3.128*7000000= | | 156-4x=32x+16 | | 17-7x=132-28x | | 215-2x=43x+20 | | 3-x=2x-3 | | 9x-7=5(2x-4) | | 6x-7=73-10x | | -10x-2x=14-8x | | 2(a+3)+3(a-1)= | | -3(4x+1)+3= | | 12.6x+5.8=9x-4.3 | | 4x+7=107-4x | | 8+(x-3)=19 | | 5x+7x=39 | | -19-2x=13-2x | | 8+(x+3)=19 | | 66-3x=42x-16 | | 59-3x=33x+15 | | x*6+126=11-14 | | t^2-9t-10=0 | | X=37.56+0.25x | | C=37.56+0.25x | | 12.6+5.8=9x-4.3 | | (-2)-3y=-6 | | 34a-4(5a+2)=32 | | 93-3x=33x+17 | | 14-7x=24-14x | | 5x^2+8x-2=0 | | 3n+3=2n+3 | | 11x-111=6x-11 |